2023
DOI: 10.3389/fgene.2023.1075824
|View full text |Cite
|
Sign up to set email alerts
|

Predicting late-stage age-related macular degeneration by integrating marginally weak SNPs in GWA studies

Abstract: Introduction: Age-related macular degeneration (AMD) is a progressive neurodegenerative disease and the leading cause of blindness in developed countries. Current genome-wide association studies (GWAS) for late-stage age-related macular degeneration are mainly single-marker-based approaches, which investigate one Single-Nucleotide Polymorphism (SNP) at a time and postpone the integration of inter-marker Linkage-disequilibrium (LD) information in the downstream fine mappings. Recent studies showed that directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The CFH gene is found on chromosome 1q31, and its protein product is a negative regulator of the complement cascade, as described above [ 50 ]. Genome-wide association studies have identified that polymorphisms in genes encoding complement factor B, complement factor H-related protein 3, complement factor I, C2, and C3 are associated with AMD in varying capacities [ 53 , 54 , 55 ].…”
Section: Activation Of the Complement System In Retinal Diseasementioning
confidence: 99%
“…The CFH gene is found on chromosome 1q31, and its protein product is a negative regulator of the complement cascade, as described above [ 50 ]. Genome-wide association studies have identified that polymorphisms in genes encoding complement factor B, complement factor H-related protein 3, complement factor I, C2, and C3 are associated with AMD in varying capacities [ 53 , 54 , 55 ].…”
Section: Activation Of the Complement System In Retinal Diseasementioning
confidence: 99%
“…In the aging retina, there is building evidence of para-inflammation in the retina over time [ 10 ]. There are many genetic factors, such as, C3 , CFH and CFHR3 , that increase the risk of late-stage AMD reported by genome-wide association studies (GWAS) [ 11 , 12 ]. Environmental risk factors, such as smoking, diet and exercise, also result in oxidative stress on RPE cells [ 13 ].…”
Section: The Role Of Inflammation In the Pathogenesis Of Geographic A...mentioning
confidence: 99%
“…Through a series of work, Li et al [19][20][21][22][23] have shown that in cancer-genomic studies, some genes, even though having weak marginal differential effects (DE), may still exude strong prediction effects on disease outcomes though regulating other strong DE genes. These weak DE genes (or weak genes), together with their coregulated strong genes and the coregulations between them, form predictive gene networks (PDN).…”
Section: Introductionmentioning
confidence: 99%